Is there a place for Traditional Chinese Medicine (TCM) in the treatment of recurrent pregnancy loss?. (August 2022) - Sun, Dingqian; Lu, Shenjiao; Gan, Xiaowen; Lash, Gendie E.
Abstract: Recurrent pregnancy loss (RPL) impacts a couple's quality of life, mental health and constitutes a large economic burden for care. Traditional Chinese Medicine (TCM) is an integrated systematic medical practice with wide clinical applications that has been predominantly used throughout Asian countries for over 2000 years. However, the efficacy of TCM in the treatment of RPL remains unclear due not only to a lack of experimental evidence, but also a lack of comprehensive summarized conclusions. Therefore, the current manuscript reviews recent relevant publications of the clinical use of TCM in RPL and illustrates its potential mechanisms. All publications (in both Chinese and English), especially randomized controlled trials (RCTs), on the use of TCM in RPL for the last ten years and research on its mechanisms were included. This review also describes our understanding of the problems and challenges in the modernization of TCM research. Highlights: TCM may be effective in the treatment of RPL. Studies are starting to investigate the mechanism by which different TCM work. Further clinical trials are required to demonstrate their effectiveness, above the rate of placebo.